Folding and Bending Planar Coils for Highly Precise Soft Angle Sensing. Issue 11 (9th October 2020) - Wang, Hongbo; Totaro, Massimo; Veerapandian, Selvaraj; Ilyas, Muhammad; Kong, Minsik; Jeong, Unyong; Beccai, Lucia
Abstract: Sensors detecting angles created by deformable structures play an increasing role in soft robotics and wearable systems. However, the typical sensing method based on strain measurement strongly depends on the viscoelastic behaviors of soft substrates and on the location of sensors that affect the sensing reliability. In this work, the changes in magnetic field coupling produced in space by planar coil deformation are investigated, for implementing a new direct transduction strategy, the soft inductive angle sensing (SIAS). A numerical analysis tool is developed for rigorously studying the inductance variations resulting from planar coils' bending, folding, and folding with a small arc. Copper or liquid metal coils, having different shapes, pitches, and sizes are built and characterized. Results show that the SIAS is hysteresis‐free, velocity‐independent, highly sensitive, ultrastable, and with fast response, guaranteeing highly precise (0.1° incremental folding angle change) and reliable measurements. It is insensitive to coil materials and to behavior of embedding soft materials, and scalable (across 10 times scale). The SIAS is adopted in three case studies (a self‐sensing origami, a sensorized soft pneumatic actuator, and a wearable sensor) to highlight its low implementation complexity, high‐performance, and versatility, providing some insights on the enormous potential of this mechanism. Abstract : The soft inductive angle sensing (SIAS) mechanism exploits the magnetic field coupling in space using film‐like planar coils that fold and bend. Unlike strain‐based sensing, this direct measurement method is hysteresis‐free, velocity‐independent, highly sensitive, ultrastable, with fast response, guaranteeing highly precise, and reliable measurement. Case studies indicate numerous potential of the SIAS for self‐sensing origami, proprioception in soft robots, and wearable sensing.